MARKETING COMMUNICATIONS IN SOCIAL MEDIA: PROBLEMS AND PERSPECTIVES - Yu. N. Slugina (Финансы: теория и практика, 2017)
This article considers marketing communications in social media as one of the most popular spheres of modern marketing allowing to support constant double-sided connection with consumers. Definitions of social media, their types and particularities are given. Social media users’ core motives, their influence on target audience loyalty and marketing communications effectiveness revelation are provided. The following structural components of marketing communications in social media like brand-platform, entertaining, useful and brand contents, ways of target audience attraction and process of marketing communications management in social media are described. The problems and difficulties of working with social media are revealed and considered: false choice of target audience and social media for communication, obligatory competences in social media sphere, must regularity in working with SMM, raise requirements for content in social media, balance maintenance between entertaining and informative content, possible lack of conversion of followers to consumers and brand ambassadors. Also perspectives of marketing mix creation is social media related to increase of social media popularity among all age groups with maximum reach of young generation, possibility of target audience parameters selection to convey a necessary message, favorableperception of company communication in social media in comparison to traditional media, interactivity, operative feedback receive, possibility of maximum wide and fast content spread which is kept in internet for a long period, ability to rich various marketing goals, possibility to use all types of marketing communications, availability of wide range of methods for marketing communications in social media evaluation are listed.